Postural balance strategies during landing at the moment of return-to-sports after anterior cruciate ligament reconstruction - Díaz, M. A.; Smeets, A.; Hagen, M.; Sankey, S. P.; Verschueren S.; Vanrenterghem, J. (Journal of Biomechanics, 2022)
Most athletes that return to sport (RTS) after Anterior Cruciate Ligament (ACL) injury undergo reconstruction (ACLR) to restore their knee stability. The major concern for RTS is for the patient to be able to perform challenging dynamic tasks whilst adequately stabilizing the knee joint and maintaining their postural balance. Nevertheless, the interaction between knee protective mechanisms (such as knee unloading and knee stabilisation) and postural balance strategies has not yet been comprehensively analyzed. Thus, the aim of this study was to investigate landing balance strategies in ACLR athletes at time of RTS. Twenty-one athletes with a unilateral ACLR were tested at the time of RTS while performing a single leg hop for distance on both limbs. Three balance mechanisms that influence the GRF during the landing phase (foot placement, center of pressure (CoP) excursion, counter-rotation of segments) were investigated and compared between the ACL injured and uninjured limb. Interactions between knee protective mechanisms and postural balance strategies were tested using a statistical parametric mapping regression analysis. Results show that CoP excursions in the injured limb increased, as well as ankle joint moment contribution to anterior-posterior (A-P) GRF. Besides, patients presenting reduced knee joint contribution to A-P GRF had to compensate with higher hip joint contribution in order to maintain postural balance. In conclusion, ACLR athletes who at RTS still protect their reconstructed knee are forced to employ compensatory postural balance strategies. Therefore, there is a persistent trade-off between knee protection and postural balance at the moment of RTS.